STEM for Everyone: A Mixed Methods Approach to the Conception and Implementation of an Evaluation Process for STEM Education Programs for Students With Disabilities - Griffiths, Amy Jane; Brady, John; Riley, Nicholas; Alsip, James; Trine, Vanessa; Gomez, Lauren (Frontiers in Education, 2021)
Some students with autism spectrum disorder and other learning differences may have superior visual acuity, increased attentional focus, and logical thinking abilities, lending to an affinity for science, technology, engineering, and mathematics (STEM) fields. At the same time, economists report that, the United States will experience a 28.2% increase in STEM-related jobs between 2014 and 2024. Although students with disabilities (SWD) can help to fill those positions, 85% of SWD graduates are either underemployed or unemployed as they enter young adulthood. Thus, there is a need to develop, evaluate, and report outcomes of STEM preparation programs specifically tailored to SWD. This mixed-methods study was designed to develop an evaluation procedure to measure a STEM school’s program for SWD and to analyze the first two years of data to help shape the evaluation process. A comprehensive evaluation model of STEM education for children with learning differences was developed and tested. Implications for practice and future research are discussed.